1990
DOI: 10.1590/s0034-71671990000100008
|View full text |Cite
|
Sign up to set email alerts
|

Promovendo o auto-cuidado: treinamento e assistência de enfermagem a pacientes portadores de bexiga neurogênica

Abstract: RESUMO -Neste trabalho, as autoras fazem algumas considerações sobre a execução da assistência de enfermagem especificamente à pacientes portadores de Bexiga Ne urogênica. A individualidade de cada paciente é considerada para que os mesmos adquiram independência no auto-cuidado e convivam da melhor maneira possfvel com as suas limitações, facilitando, desta forma, sua reintro dução na vida familiar e social. Apresentam uma sonda de vidro confeccionada no Hospital das Clfnicas da Faculdade d e Medicina de Ribei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 5 publications
0
8
0
3
Order By: Relevance
“…The year with the highest number of published articles was 2011 with three studies (16)(17)(18) , followed by 2002 and 2015 (19)(20)(21)(22) , both with two studies each. It should be noted that the earliest study that addresses the theme dates back to 1990 (23) , and the most recent is from 2016 (24) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The year with the highest number of published articles was 2011 with three studies (16)(17)(18) , followed by 2002 and 2015 (19)(20)(21)(22) , both with two studies each. It should be noted that the earliest study that addresses the theme dates back to 1990 (23) , and the most recent is from 2016 (24) .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the language, nine articles (16)(17)19,(21)(22)(24)(25)(26)(27) were published in English, and four in Portuguese (18,20,23,28) . In relation to the databases, five were identified in the MEDLINE/ PubMed (21,(24)(25)(26)(27) , five in the LILACS (17)(18)20,23,28) , two in the CINAHL (16,19) and one in the SCOPUS (22) . It should be noted that the four studies identified in Portuguese were carried out in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…O tratamento é estritamente cirúrgico de caráter emergencial para a descompressão posterior ao nível da C1. 12 Como em praticamente todos os casos, quanto antes o diagnóstico melhor será o prognóstico…”
Section: Malformação De Arnold Chiari Tipo IIunclassified
“…Alguns autores recomendam realizar a lavagem exterior com água e sabão e depois enxaguar o interior com água corrente, secar com toalha limpa e manter em lugar seco, dentro de um recipiente limpo 17,18 . Outros, orientam lavar os cateteres com água e sabão e ferver por 10 minutos 19,20 .…”
Section: [] Lubrifico a Sonda Com A Pomada X Uso Bem Pouquinho Nunclassified